2014
DOI: 10.1590/0004-282x20140127
|View full text |Cite
|
Sign up to set email alerts
|

Cognition in a multiple system atrophy series of cases from Argentina

Abstract: Cognitive dysfunction may occur in 17-40% of patients with multiple system atrophy (MSA). It has been suggested a milder cognitive impairment in cerebellar (MSA-C) than in parkinsonian variant (MSA-P). However, differences in cognitive profiles remain under discussion. Objective: To evaluate cognitive features in a series of patients with "probable MSA" from Argentina. Method: After informed consent was obtained, an extensive cognitive tests battery was administered. Nine patients (6 MSA-P and 3 MSA-C) compose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…So far, few studies have addressed the possible differences between patients with predominant cerebellar or parkinsonian presentation, and the focus has been mainly on MSA‐P patients. In this study, a comparison of raw scores revealed lower performance of MSA‐C patients than MSA‐P patients in a screening of executive functions and in phonological verbal fluency.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…So far, few studies have addressed the possible differences between patients with predominant cerebellar or parkinsonian presentation, and the focus has been mainly on MSA‐P patients. In this study, a comparison of raw scores revealed lower performance of MSA‐C patients than MSA‐P patients in a screening of executive functions and in phonological verbal fluency.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, there are conflicting results and heterogeneous data have been published regarding the differences between MSA‐C and MSA‐P. Previous studies suggested a comparable performance, a more prominent decline of executive function and verbal memory in MSA‐C or a more pronounced cognitive dysfunction in MSA‐P …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations